WAKAF KOLEKTIF DAN PENGELOLAANNYA DALAM PERSPEKTIF HUKUM ISLAM: Studi Kasus Yayasan Dharma Kasih Jakarta Timur - Suharwoto; Ahmad Asrof Fitri; Ali Aminulloh (Melati Institute, 2023)
Management and management of waqf in Indonesia is still a cause for concern. As a result, quite a lot of waqf assets have been neglected in their management, and some waqf assets have even been lost. The aims of this study were: 1) to find out the description of collective waqf management at the Dharma Kasih Foundation, East Jakarta. 2) to obtain an explanation regarding the Islamic Law review of the collective waqf process carried out by the East Jakarta Dharma Kasih Foundation. This research is a qualitative research using a qualitative descriptive approach. The type of this research is field research. Data collection techniques were carried out in 3 ways, namely: 1) interviews, 2) observation, 3) documentation. The results of the study are (1) the management of the collective waqf of the East Jakarta Dharma Kasih Foundation, namely for land acquisition for the expansion of the foundation and the construction of the foundation's prayer room. It was recorded that there were 122 w?qifs for land acquisition for the foundation and 137 w?qifs for the construction of the foundation's prayer room. (2) Collective endowments for expanding the land of the East Jakarta Dharma Kasih Foundation for mosques and building a prayer room in accordance with Islamic law are permitted. Judging from the perspective of fiqh, it has fulfilled the pillars and conditions, namely w?qif (a person who donates property), mauquf bih (goods or property that is donated), mauquf'alaih (the party who is given waqf / designation of waqf), shighat (a statement or pledge of w?qif as a will to donate part of their property). In the perspective of the waqf law, the waqf elements have also been fulfilled, namely waqif, nazhir, waqf assets, waqf pledges, allotment of waqf assets and the waqf period.